Pengaruh Posisi Titik Rekombinasi Terhadap Unjuk Kerja GLCC Metering Loop - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This paper presents performance of a gas-liquid cylindrical cyclone separator (GLCC metering loop). The effects of outlet position on the GLCC metering loop separator have been studied experimentally. New experimental data were collected utilizing a 7.62cm ID, 150cm high GLCC, which has a single inlet system. Parameters investigated, included six different positions of a recombination point (H=80, 60, 40, 20, 0, and -20cm from the inlet plane). The results were presented in graphical form of the equilibrium liquid level (Leq) as a function of the superficial gas velocity (vsg). Leq increased with the recombination position. A good agreement was obtained between the theory and the experiments.